(untitled) (International Journal of Physiotherapy, 2015)
Background: Neck pain is a common problem within our society. Upper trapezius sternocleidomastoid and the levator scapulae are the most common postural muscles that tends to get shorten leading to restricted neck mobility. There is lack of evidence to allow conclusions to be drawn about the effectiveness of post isometric relaxation when compared with static stretching exercises. The aim is to find out the effectiveness of Post isometric relaxation Versus Static stretching in the subjects with chronic nonspecific neck pain. To evaluate the effectiveness of post isometric relaxation technique on pain by using Visual analoge scale, range of motion by using Universal Goniometry, and functional disability by using Neck Disability Index in chronic nonspecific neck pain. Methods: A convenient sample of thirty seven subjects was diagnosed with nonspecific neck pain was randomly allocated to one of the two treatment groups on the basis of the inclusion criteria. The experimental group (n=15) received three sessions of post isometric relaxation technique for trapezius, sternocleidomastoid and the levator scapulae and control group (n=15 received the three sessions of static stretching for trapezius, sternocliedomastiod and levator scapulae for four weeks. Results: Non parametric tests demonstrated a statistically significant difference with experimental group showing greater improvement in ROM, VAS, and NDI than the control group and significant difference within the group also. Conclusion: This study concluded and the results reflected that post isometric relaxation technique group had better improvement in reduction of pain, improvement in the range of motion, and increased neck functional activities than the static stretching group.